“In A.I. we trust?” The effects of parasocial interaction and technopian versus luddite ideological views on chatbot-based customer relationship management in the emerging “feeling economy” - Youn, Seounmi; Jin, S. Venus (Computers in human behavior, 2021)
Despite the hype surrounding Artificial Intelligence (AI), the potential of AI in customer relationship management (CRM) remains underexplored in academia. A between-subjects experiment examined the effects of the type of relationship (virtual assistantship versus virtual friendship) consumers build with AI-enabled chatbots on brand personality perception, parasocial interaction (PSI), and CRM. The main effects of the relationship type on brand personality perception appeared for competent brand personality, but not for sincere brand personality. The consumer-chatbot relationship type had effects on CRM-related outcomes (behavioral intention, satisfaction, and trust) through competent brand personality. Consumers who interacted with a friend chatbot experienced stronger PSI with the chatbot, and the relationship type had an influence on brand personality perception through PSI. This mediating effect of PSI was observed for both brand personalities - competence and sincerity. The moderating role of ideological views (technopians versus luddites) in explaining the effect of the relationship type on brand personality perception was detected for sincere brand personality. AI designers and marketers need to develop AI user interface (UI) and user experience (UX) along with marketing strategies that not only can appeal to technopians ready to adopt innovative AI customer representatives but also can ultimately help alleviate luddites’ AI anxiety in the emerging “feeling economy” envisioned by Rust and Huang. •Chatbots can form virtual assistantship versus virtual friendship with customers.•Chatbots can represent a brand in customer relationship management (CRM).•Brand personality perception and parasocial interaction (PSI) affect CRM.•Virtual friend chatbots induce stronger PSI than virtual assistant chatbots.•Technopians and luddites respond differently to AI-manifested brand personality.